Impacts of climate and land-use changes on water yields: Similarities and differences among typical watersheds distributed throughout China - Qian Guo; Chunxue Yu; Zhihao Xu; Ying Yang; Xin Wang (Journal of Hydrology: Regional Studies, 2023)
Study region: Seventeen watersheds distributed throughout China Study focus: Climate and land-use changes result in significant impacts on watershed water yields. The water yield response to climate and land-use changes differs due to variations in watershed geographical, climatic, and socioeconomic characteristics. Effects of watershed characteristics on water yield response remain unclear. In this study, the InVEST model is used to simultaneously assess water yields of 17 typical watersheds distributed throughout China, with widely differing characteristics, and specific scenario simulations are conducted to compare similarities and differences among different watersheds in the water yield response to climate and land-use changes. New hydrological insights for the region: Results show that about three quarters of the investigated watersheds are characterized by increasing water yields from 1990 to 2020. The impact of climate change on water yield is similar in these watersheds. However, water yield response to land-use changes exhibits significant spatial differences, which is affected by watershed geographical and climatic characteristics. The mean annual water yield of Hai River watershed with two megacities (Beijing and Tianjin) is lowest among investigated watersheds, which is only 0.14 % of that in the Min River watershed in southeastern China. This implies that the mismatch of regional socioeconomic development and water availability remains a big challenge in China and requires rational cross-watershed management strategies.